2008
DOI: 10.1111/j.1365-2249.2008.03714.x
|View full text |Cite
|
Sign up to set email alerts
|

Allergy and the cardiovascular system

Abstract: SummaryThe most dangerous and life-threatening manifestation of allergic diseases is anaphylaxis, a condition in which the cardiovascular system is responsible for the majority of clinical symptoms and for potentially fatal outcome. The heart is both a source and a target of chemical mediators released during allergic reactions. Mast cells are abundant in the human heart, where they are located predominantly around the adventitia of large coronary arteries and in close contact with the small intramural vessels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
149
0
16

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(169 citation statements)
references
References 39 publications
4
149
0
16
Order By: Relevance
“…Anaphylactic shock is sometimes life-threatening and accompanied by cardiac manifestations, which are clinically characterized by acute myocardial ischemia via coronary artery spasm and left ventricular (LV) dysfunction [1][2][3][4][5][6][7][8]. Allergic activation of cardiac must cells is known to be of particular importance as a cause of the acute coronary syndrome, which is called "Kounis syndrome" [9].…”
Section: Introductionmentioning
confidence: 99%
“…Anaphylactic shock is sometimes life-threatening and accompanied by cardiac manifestations, which are clinically characterized by acute myocardial ischemia via coronary artery spasm and left ventricular (LV) dysfunction [1][2][3][4][5][6][7][8]. Allergic activation of cardiac must cells is known to be of particular importance as a cause of the acute coronary syndrome, which is called "Kounis syndrome" [9].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of mast cells in the heart and the release of cardiotoxic mediators such as histamine, LTC4, and platelet-activating factor [21], as well as the increase in mast cell counts in the coronary vessels of patients with ischemic heart disease, can render the heart incapable of overcoming the systemic and cardiac effects of anaphylaxis. In addition, the widespread concomitant use of β-blockers and ACE inhibitors in cardiovascular diseases [22,23] has been considered to cause more severe anaphylaxis in patients with heart disease [24]. Our literature review [5,6,24,25] revealed that several markers can be used to assess the severity of anaphylaxis and that not all markers of cardiovascular disease are associated with all severity markers.…”
Section: Discussionmentioning
confidence: 99%
“…Yıllık insidansının çocuklarda 75.1/100.000, adölesanlarda ise 65.2/100.000 olduğu bilinmektedir [2]. Çocukluk çağında meydana gelen anaflaksiye bağlı mortalite oranları %0.7 ile %20 arasında değişmektedir [3,4]. Anafilaksiye neden olan en önemli etkenler besinler (%33), venomlar (%19) ve ilaçlardır (%14) [2].…”
Section: Introductionunclassified